PERSONALIZED MARKETING STRATEGIES: HOW TO TAILOR OFFERS AND SERVICES TO EFFECTIVELY MEET CUSTOMER NEEDS - Ali faron abd; Osamah Ali Mashkoor; Ameer Naser Hussein (Scholar Express Journals, 2024)
Marketing is the lifeblood of all businesses. In businesses with specialized products/services, a personalized marketing strategy is recommended. This research is conducted using a qualitative-quantitative combined method to determine the constructive suggestions of meeting with the customer with the approach of marketing strategy. The statistical population includes all the heavy woodworking companies in the Iraq, in the first part, the junior and senior managers of these companies and in the second part, all their customers are considered. After studying the theoretical foundations, planned interview questions, and after implementation in a sample of ten people, four main factors were identified and finally, after distributing the questionnaire among the sample of one hundred people, four sub factors were determined for each main factor. The final result is that for the mentioned purpose, the most important factor is "accuracy in customer selection" with four sub-factors: 1- homogeneousness, 2-continuous presence, 3-purchase history and 4-attention to personality; For the second factor centered on "determining the right time", four sub-factors were determined: 1- attention to busyness, 2- flexibility in agreed time, 3- shortness of interview and 4- attention to fatigue. The third factor includes "Targeted selection of questions" which includes four subfactors:1-Brief questions.2-Questions based on theoretical foundations.3- Proportionality with facilities.4-Highlighting suggestions. The last factor "Preserving customer respect" includes the following sub-factors:1-Proper hospitality.2Appropriate behavior.3-Apologizing for taking time.4-Not suggesting an answer
Keywords: Marketing Strategy; Meeting; Specialized Businesses